The Influence of Concentrace Mineral Drops on Performance Broiler - Mugiyono, Sigit (ANIMAL PRODUCTION, 1999)
A research has been conducted in Experimental Farm Faculty of Animal Husbandry Unsoed from July 1 st until August 15 th, 1996. The purpose want to study the influence of CMD supplementation in drinking water consists of M0 = control; M1 = 0.5 drops/1000 cc, M2 = 1 drops/1000 cc; M3 = 1.5 drops/1000 cc and M4 = 2 drops/1000cc. The performance observed were growth, body weight, feed consumption, feed conversion, drinking water consumption; and income over feed and mineral cost (IOFMC). The research involved 100 broiler chickens divided that CMD supplementation until 2 drops/1000cc did not significantly affect on the performance of broiler chickens except in income over feed and mineral cost (P<0.05). (Animal Production 1(2): 56-62 (1999)Key Words: broiler, concentrace mineral drops, performance.